Mycoplasma hyorhinis induces proinflammatory responses in mice lymphocytes. (11th July 2014) - Kornspan, Jonathan D.; Tsur, Maayan; Tarshis, Mark; Rottem, Shlomo; Brenner, Talma
<x xml:space="preserve">Abstract</x> Mycoplasmas are frequent contaminants of cultured cells, leading to alterations in cellular gene expression, protein synthesis, signal transduction, and metabolic pathways. Mycoplasma hyorhinis, the major contaminant of tissue cultures, has been implicated in a variety of diseases in swine. Most human and animal mycoplasmas remain attached to the surface of epithelial cells. Nonetheless, we have recently shown that M. hyorhinis is able to invade nonphagocytic melanoma cells. In the present study, we show by confocal laser scanning microscopy, that by exposing mice splenocytes to intact M. hyorhinis, intracellular mycoplasmas were detected. Mycoplasmal components were not detected within splenocytes after exposure to heat inactivated M. hyorhinis or to a purified M. hyorhinis lipoprotein (LPP) fraction. However, incubation of the splenocytes with intact M. hyorhinis cells, heat inactivated cells or M. hyorhinis LPP fraction induced accelerated cell proliferation and the secretion of interferon gamma and interleukin 17. Thus, M. hyorhinis and its LPPs can be added to the list of infectious agents causing direct stimulation of proinflammatory responses by mammalian lymphocytes.